Tutorial computer-assisted language learning. (8th September 2015) - Heift, Trude; Schulze, Mathias
<x content-type="archive" xml:space="preserve">Abstract</x> 'Sometimes maligned for its allegedly behaviorist connotations but critical for success in many fields from music to sport to mathematics and language learning, practice is undergoing something of a revival in the applied linguistics literature' (Long & Richards 2007, p. xi). This research timeline provides a systematic overview of the contributions of computer-assisted language learning (CALL) to the role, nature, and development of individual practice in language learning. We focus on written language practice in Tutorial CALL, corrective feedback and language awareness-raising in Intelligent CALL (ICALL), and individualization of the learning process through tailoring of learning sequences and contingent guidance.